Infection control practices among nursing staff in ICUs - Kalafati, Maria; Kalograna, D; Lemonidou, Chryssoula; Merkouris, Anastasios (My University, 2001)
Introduction: Although infections are spread in hospitals mainly by hands and the accidents with needles are not rare, the staff shows a low compliance with the infection control guidelines. Objective: To evaluate the compliance of nursing personnel with the infection control guidelines in Intensive Care Units (ICUs) and explore possible relationships with background factors. Method: A descriptive, exploratory design was adopted by using a self-completed questionnaire. (N=127, 12 ICUs from three hospitals). Results: Nurses reported a high level of knowledge regarding the infection control (M=1.86, SD=0.66, R=0-3), but most of them (70.9%) had never participated in continuous education programs or seminars and they wanted to learn more (98.4%). Males reported a lower level of Knowledge (1.29 – 1,95 P<0,05) and they had a more negative attitude (1,24 – 2,12 P<0,05). The compliance varied from 30,7% for hand washing to 96,9% for use of gloves (M=2.14; SD=0.70; R=0 -3). Nursing personnel with higher education and experience more than 5 years reported higher compliance with specific practices. Statistical differences were found between hospital regarding the attitude and the availability of the basic consumable materials. Conclusion: More in-service education in specific areas, motivation of staff, and integration of the infection control into a quality assurance program are necessary steps in order to increase the compliance of the staff.